DEKONSTRUKSI AKTING DALAM PERTUNJUKAN TEATER UNDER THE VOLCANO KARYA/SUTRADARA YUSRIL DALAM TINJAUAN ESTETIKA POSMODERN - Ilham Rifandi; Andar Indra Sastra; Sahrul N (Puitika, 2018)
This study aims to explore the deconstructive tendency of acting in the performances of Yusril's Under the Volcano works / director. The acting device of an actor also develops according to the situation of society and culture. Actors in postmodern culture no   longer analyze the soul, or present patterns of human behavior as Stanislavsky suggested. The actor explores his mental state through the postmodern aesthetic idioms that tend to be artificial, a culture that worships form. In the Under the Volcano theater performance, the concretization process of actor work was born through Minangkabau traditional arts. The research methods used in this study are: Observation, documents, interviews and data analysis. The results of this study indicate that, in the concrete process of work in postmodern culture there are aesthetic idioms built through silek, dendang, poetry and poetry texts which are then implemented in the form of acting that emphasizes the use of gestural acting, prescribes verbality and tends to be acrobatic.  Keywords: postmodern aesthetics, acting, Under the Volcano